An introduction to the 'Oceans and Society: Blue Planet' initiative. (20th November 2019) - Smail, Emily A.; DiGiacomo, Paul M.; Seeyave, Sophie; Djavidnia, Samy; Celliers, Louis; Le Traon, Pierre-Yves; Gault, Jeremy; Escobar-Briones, Elva; Plag, Hans-Peter; Pequignet, Christine; Bajona, Lenore; Zhang, Li; et al.
ABSTRACT: We live on a blue planet, and Earth's waters benefit many sectors of society. The future of our blue planet is increasingly reliant on the services delivered by marine, coastal and inland waters and on the advancement of effective, evidence-based decisions on sustainable development. 'Oceans and Society: Blue Planet' is an initiative of the Group on Earth Observations (GEO) that aims to ensure the sustained development and use of ocean and coastal observations for the benefit of society. The initiative works to advance and exploit synergies among the many observational programmes devoted to ocean and coastal waters; to improve engagement with a variety of stakeholders for enhancing the timeliness, quality and range of information delivered; and to raise awareness of the societal benefits of ocean observations at the public and policy levels. This paper summarises the role of the initiative, current activities and considerations for future directions.